Competence (Knowledge, Attitudes and Skills) Midwifeve to Handling of Obstetric Emergency According to Standard Operational Procedures - Tetty Ripursari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
One of the efforts to reduce maternal mortality rate is to improving the quality of service handling obstetric emergency by midwife. The purpose of the research is to analyze the competence (knowledge, attitude and skill) of midwife against the handling of obstetric emergencies in the City of Blitar. The desain used in the research is analytic quantitative. Population are all midwives in Blitar City of 158 people. The sample size is 113 rspondents, using simple random sampling tehnique. Independent variable of is knowledge, attitude and sklill, dependent variable is handling of obstetric emergency according to Standard Operational Procedures (SOP). Data collected by questionnaire and observation then analized using logistic regression. Statistical test result obtained that the knowladege variables p value 0,042 < α = 0,005, meaning that knowledge have an effect the handling of obstetric emergency, attitude variable p value 0,003 < α = 0,05, meaning attitude have an effect on handling of obstetric emergency, skill variable p value 0,038 < α = 0,05, meaning skill have an effect on handling of obstetric emergency. The lowest/smallest variable is the attitude variable, where the p value is 0,003 < α = 0,05, meaning that dominant factor that influences the handling of obstetric emergencies according to SOP is the attitude variable. Knowledge, attitudes and skills of midwives affect the handling of obstetric emergencies according to SOP in the City of Blitar